2019
DOI: 10.1111/jwas.12620
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological water quality of recirculating aquatic systems for maintenance of yellowtail amberjack Seriola lalandi

Abstract: The bacteriological water quality associated with marine fish farming systems can be a determining factor in the development of disease, and understanding this quality is fundamental for the prevention and control of possible disease outbreaks. In the present study, the bacteriological water quality of a yellowtail amberjack Seriola lalandi broodstock maintenance system, composed of two units of a recirculation aquaculture system (RAS 1 and RAS 2), was determined. From February 2016 to January 2017, monthly sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(62 reference statements)
2
2
0
Order By: Relevance
“…Additionally, the opposite result was observed when feeding was done four days prior to the count, which was reduced in comparison to the preceding counts. This is in accordance with preview works showing that the number of bacteria can be affected by a number of factors, such as the organic matter load of food (Alfiansah et al, 2018;García-Mendoza et al, 2019;Heenatigala & Fernando, 2016;Leonard et al, 2002;Qin et al, 2016;Vasile et al, 2017) Sea urchins are known to be susceptible to poor water quality, especially when ammonia levels are high (Basuyaux & Mathieu, 1999;Lawrence et al, 2003;Rubilar & Crespi-Abril, 2017;Siikavuopio et al, 2004). Although some of the physicochemical parameters in this investigation were higher, it did not affect the welfare of the animals.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the opposite result was observed when feeding was done four days prior to the count, which was reduced in comparison to the preceding counts. This is in accordance with preview works showing that the number of bacteria can be affected by a number of factors, such as the organic matter load of food (Alfiansah et al, 2018;García-Mendoza et al, 2019;Heenatigala & Fernando, 2016;Leonard et al, 2002;Qin et al, 2016;Vasile et al, 2017) Sea urchins are known to be susceptible to poor water quality, especially when ammonia levels are high (Basuyaux & Mathieu, 1999;Lawrence et al, 2003;Rubilar & Crespi-Abril, 2017;Siikavuopio et al, 2004). Although some of the physicochemical parameters in this investigation were higher, it did not affect the welfare of the animals.…”
Section: Discussionsupporting
confidence: 91%
“…The research performed by Garcia‐Mendoza et al. (2019) revealed that the phylum Proteobacteria was predominant in the culturing water of the yellowtail kingfish, including the orders Vibrionales and Alteromonadales (≈60%), whereas Bacteroidetes was the most dominant phylum detected in our study. This is because the approach used contemplated the metagenomics DNA present in water, whereas the former approach considered cultivated bacteria only.…”
Section: Figuresupporting
confidence: 53%
“…(2017) argued that the microbiota in commercial‐scale recirculating and semi‐closed aquaculture systems rearing Atlantic salmon ‘can potentially have a great impact on the robustness and health of the fish’. Garcia‐Mendoza, Cáceres‐Martínez, Vásquez‐Yeomans, and Cruz‐Flores (2019) argued that the bacterial community contributed to the maintenance of a balance of the recirculation system of the yellowtail kingfish, preventing the development of infectious diseases; however, this approach contemplated targeted 16S rRNA gene amplification of bacteria cultured in trypticase soy agar supplemented with 2% NaCl. Detailed reports derived from DNA shotgun sequencing of bacterial communities thriving in the culturing systems of the yellowtail kingfish are still absent.…”
Section: Figurementioning
confidence: 99%
“…They become pathogenic when conditions such as temperature changes, dietary, hormonal stresses and other physiochemical parameters are favourable for the development of pathogenesis 13 , the condition that fishes are cultured may be potentially stressful.…”
Section: Introductionmentioning
confidence: 99%